Mechanical Response and FEM Modeling of Porous Al under Static and Dynamic Loads. Issue 3 (4th October 2013) - Michailidis, N.; Smyrnaios, E.; Maliaris, G.; Stergioudi, F.; Tsouknidas, A.; Stephani, Günter; Scheffler, Michael
<x xml:space="preserve">Abstract</x> Metal foams were produced to experimentally investigate their crush behavior and compare with computational results. The representation of the foam complex geometry is possible by employing Non Uniform Rational B‐Splines (NURBS), allowing for a successful and fail‐free volume discretization to finite elements. The foam geometry is produced by combining a parametric 3D Voronoi cell volume partitioning with sophisticated CAD algorithms. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>